Nurcholish Madjid's Neo-Modernism in Substantive Islamic Movements in Indonesia - Yufriadi, Ferdi; Syahriani, Fadilla; Afifi, Abdullah A (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2023)
At this time, there is a stagnation of thought among Muslims regarding whether the concept of an Islamic state is still being debated or not. Islamic socio-political movements are divided into two streams, namely Substantive Islam and Symbolic Islam. Nurcholish Madjid firmly rejects the politicization of Islam in the interests of political groups that are members of Islamic parties. With the motto: "Islam Yes, Islamic Party No!". According to Nurcholish Madjid, Islamic political power is not always related to Islamic parties. He tries to convey a more substantial view of Islam, not just symbolism. Seeing the current situation, the criticism conveyed by Nurcholish Madjid is still very relevant. This research was conducted to explore the relevance of Nurcholish Madjid's thoughts on state politics in Indonesia by considering the current situation. Based on the results of this research, it was revealed that Nurcholish Madjid chose Islam which is more substantial than just symbolism. This has its roots in the universal values of Islam, not just the symbol of the "Islamic party" itself. If we look at the current situation, the criticism raised by Nurcholish Madjid is still relevant because, at this time, the politicization of religion is generally used to attack political opponents or increase party electability. Instead of using Islam as a moral guide for politics, political elites tend to use Muslims for individual interests.